Effect of Particle Property on Coagulation and Degradation of Residual Rubber in Natural Rubber Wastewater - Daisuke Tanikawa, (International Journal of Integrated Engineering, 2025)
In natural rubber (NR) wastewater treatment, removal of residual rubber is necessary to apply closed anaerobic system for reduction of greenhouse gases emission. In this study, a combined system of an anaerobic baffled reactor (ABR) and a down-flow hanging sponge (DHS) reactor with a pretreatment canal (PTC) for NR wastewater treatment were applied to evaluate the effect of particle property on residual rubber removal. In NR wastewater, major particle sizes of residual rubber were more than 1.0 µm, 0.45–0.1 µm and less than 0.1 µm. At an early stage of the PTC, smaller particle sizes of residual rubber were reduced, while middle particle sizes were increased. In contrast, at a later stage of the PTC with increasing biodegradability, larger particle sizes of residual rubber were reduced, while smaller particle sizes of residual rubber were increased. As residual rubber removers, Acinetobacter and Pseudomonas are detected for biological coagulation and degradation of residual rubber in the PTC, respectively. In contrast, predominant rubber-degrading bacteria in the DHS reactor is Gordonia. The early and later stages of the PTC function as rubber coagulation and rubber degradation stages, respectively. Furthermore, Pseudomonas and Gordonia are considered degradation bacteria for liquid rubber and solid rubber, respectively.